Alexander McQueen : the life and the legacy - Watt, Judith (Harper Design, 2012)
An intimate and revealing look at the personal and professional life of the fashion world's most visionary designer. This volume strips away the layers of legend surrounding Alexander McQueen, revealing the sartorial genius and the true history of the man who reinvented modern fashion. Uncovering new details about Lee Alexander McQueen's humble childhood in East London, author Judith Watt traces the young designer's ascent--from his graduate collection at Central Saint Martins School of Art and Design to his over-the-top runway shows to the designs he created just days before his death at age forty. Providing new insights into the dark passion and inspiration that guided each fever-pitched runway show, this fully illustrated portrait delivers a comprehensive, in-depth look at the most provocative designer of a generation. Illustrated throughout with McQueen's personal drawings and ephemera as well as a mixture of exquisite catwalk and editorial fashion images.--From publisher description.